Analisis Tata Letak Rak Pada Toko Retail Menggunakan Metode ARC Dan TCR : Studi Kasus Pada Supermarket X - Arief Hermawan; Cempaka Chandra Kirana; Fayza Andani; Gina Natasya Novitasari; Mochammad Azriel Fahrezi; Khoirul Aziz Husyairi; Tina Nur Ainun (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Supermarket x is a retail shop that sells various types of products ranging from home necessities, kitchen necessities, food and drinks. The importance of layout in retail is needed to make it easier for consumers to reach the goods they need. Supermarket x has a less effective layout, especially in arranging display shelves. This research aims to make recommendations for layout, especially new display shelves that are more efficient so that consumers can easily reach the items they want to buy. This research uses the Activity Relationship Chart (ARC) and Total Closeness Rating (TCR) analysis methods. The results of the research show that there is a change in the placement of goods on display shelves, after using ARC and TCR, the placement of goods on display shelves is arranged based on the closeness grouping of goods types, shelves 4 and 5 have a value of A (absolute) so the shelves must be close together, while shelf 2 with shelves 4, 5, 6, and 7 have undesirable adjacent X (prohibited) values. Shelf 5 which contains snacks has a high ARC value of 121, so shelf 5 will be allocated first, because snacks are most often sought after by consumers.